Cover Cropping Increases Soil Fungal-Bacterial Community Diversity and Network Complexity in Apple Orchards on the Loess Plateau, China - Liu, Chong-Yi; Wang, Ying-ying; Chen, Xin-yi; Tan, Hua; Jin, Xu-mei; Lu, Qi; He, Shu-bin; Long, Ming-Xiu (Frontiers in Environmental Science, 2022)
Soil microorganisms play a key role in soil fertility. Exploring the microbial community composition and diversity in response to cover crops is important for improving soil fertility in orchards. This study investigated how cover cropping can improve soil fertility by altering microbial community composition and the interrelations among soil microorganisms. Soil physicochemical and biological indicators and microbial community composition were evaluated after a 6-year application of cover cropping in an apple (Malus pumila cv. Fuji) orchard located on the Loess Plateau, China. Three treatments were applied: Trifolium repens treatment (TR), Lolium perenne treatment (LP), clear tillage treatment (CT). The soil of the cover crop treatments had a more complex microbial co-occurrence network than that of the clear tillage treatment; in particular, the correlations among fungi were significantly increased. Cover cropping increased the levels of soil organic matter (SOM), microbial biomass carbon (MBC), and total nitrogen (TN) in orchard soil. Changes in the fungal community were more related to microbial biomass nitrogen (MBN), TN, and carbon-nitrogen ratio (C:N). This indicates that cover cropping not only increases the diversity of soil microorganisms but also increases the interrelations between microbial groups, thereby improving the soil fertility of apple orchards on the Loess Plateau.